A review of complex in vitro cell culture stressing the importance of fluid flow and illustrated by organ on a chip liver models - Wilkinson, John Malcolm (Frontiers in Toxicology, 2023)
The translation of new technology from development into widespread commercial use is a complex and time-consuming process that requires significant investment. This review looks at underlying market needs, the technical difficulties that must be overcome, particularly those connected with the use of microfluidics, and also addresses the economics. Despite the strong ethical arguments for replacing the use of animals in drug safety testing and medical research, the author believes that financial benefits of adopting the new in vitro technology are becoming clear and will drive the adoption by industry.